The role of the Financial guarantee mechanism for loans in supporting small and medium enterprises - Medkour, Sarra; Boulahlayes, Ilhem (Journal of Human Sciences, 2023)
Bank financing is considered one of the basics of establishing and expanding the activities of small and medium enterprises of all kinds. However, the problem of providing guarantees is one of the most important obstacles that the investor faces in obtaining a loan. Therefore, in recent years, the public authorities have paid attention to these institutions within the framework of the state’s policy aimed at supporting and developing this sector. The government to create new financing mechanisms and alternatives by stipulating in its legislation the establishment of a set of structures that support the relationship between the bank and the institution by granting a financial guarantee contract that complements the well-known classic guarantees in the event that they are insufficient to cover the risks resulting from non-payment, insolvency or bankruptcy of the institution, and thus the risk is shared loan with the bank.